Kajian Kepuasan Pasien Terhadap Pelayanan Kefarmasian Di Apotek Rawat Jalan RSUD Sungai Dareh - Rizal, Rosiana; Shandy, Vira Ry; Rusdi, Mesa Sukmadani; Afriyeni, Helmice (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2024)
Pharmaceutical services are a direct and responsible service to patients related to pharmaceutical preparations that intend to achieve definite results to improve the quality of life of patients. Patient satisfaction is an element that is often used as a benchmark in assessing the quality of service in hospitals. The purpose of this study was to find out the level of satisfaction with pharmaceutical services at the outpatient pharmacy of Sungai Dareh Hospital. Research uses quantitative methods with a cross sectional approach. The number of samples analyzed as many as 120 people were taken with random sampling techniques, data collection using questionnaires and analyzed with quantitative analysis. From the results of this study, the level of patient satisfaction with pharmaceutical services at the Outpatient Pharmacy of Sungai Dareh Hospital from the total of all dimensions with a percentage of 82.51%. In the dimension of direct evidence(Tangible) has the highest level of satisfaction with a percentage of 84.55%, the reliability dimension (Reliability) with a percentage of 82.70%, the responsiveness dimension with a percentage of 82.70%, the empathy dimension (Empaty) has the lowest satisfaction rate with a percentage of 79.49%, and the dimension of assurance (Assurance) with a percentage of 82.49%